Personality Profile of a Group of Cyto-Histotechnology Students - Volmar Quintero, Luis; Castro M., Carlos A.; Flórez Sierra, Alex (TECCIENCIA, 2017)
By 2012, the National Ministry of Education in Colombia recognized 286 Institutions of Higher Education (IHEs) in the country that offered technical and technological programs. The quality of technicians, technologists, and other professionals is directly related to their performance during secondary and tertiary education. The aim of this paper is to describe the personality profile and academic performance of a group of Cytology and Histology students at a Health Sciences institution of higher education. We performed a descriptive study that included first to third semester students in the Department of Cytology and Histology. We measured socio-demographic variables related to academic achievement and the Gordon Personal Profile-Inventory (GPP-I) test results. This study was approved by the Ethics for Research on Humans Committee at the Fundación Universitaria de Ciencias de la Salud. We analyzed 53 Cytology and Histology students. The average age was 18 years old (IQR 18-21), and the gender distribution was 88.4% female (46/53). The initial grade mean was 3.5 (IQR: 3.3-3.8), with 5 being the maximum in the Colombian grading system, and the mid-career grade was 3.7 (IQR: 3.6-4). We explored the relationship between the place of residence before starting the program, the result of the National Test for Graduates in Colombia (ICFES-SABERPro, comparable to the American SAT), and the academic performance of students. We observed a significant correlation among these variables. Despite there being a number of university departments in the field in Colombia, Cytology/Histology is a poorly known profession, and the skills and abilities together with its range of tasks in the labor market are unknown. Concerning academic performance and its correlation with the GPP-I domains, we observed that there was a direct relationship between starting grade point average and original thinking.